SUICIDAL HANGING:A PROSPECTIVE STUDY (Journal of Forensic Medicine & Toxicology, 2018)
The objective of this study was to focus on various factors associated with suicide by hanging at Ahmedabad, India; with a view to identify causating factors. A prospective study was carried out on 274 cases of death  due to suicide by hanging which was received by the Deparment of Forensic Medicine, B. J. Medical College, Ahmedabad, India, during the period of 1st January 2012 to 31st December 2012. In the present study, 87% of the cases were below the age of 40 years and 58.76% were married. The main precipitating factors in the majority of cases were Unknown (33.21%), others were marital unhappiness  (13.87%), problems associated with Love Affairs (12.77%). To reduce the incidence of suicides by hanging, there is urgent need to focus on these factors.
Keywords: Suicide; Hanging; Precipitating Factor